The Swedish theory of love individualism and social trust in modern Sweden - Berggren, Henrik; Trägårdh, Lars (New directions in Scandinavian studies, 2022)
"Drawing on work in philosophy, cultural studies, sociology, literary criticism, and political science, The Swedish Theory of Love shines a light on the workings of individualism in a far from utopian order of things"--